PENERAPAN TEKNIK SCRAMBLE WACANA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 32 BANDA ACEH - Cut Marlini; Yusrawati JR Simatupang (Jurnal Tunas Bangsa, 2017)
This study is aimed to improve reading comprehension ability of the fourth grade students of SDN 32 Banda Aceh. This research is based on the problems found in the class that the students look less excited due to the monotonous method used by the teacher in presenting the material to the students. The teacher only provides reading text to students and then the students were asked to answer questions from the reading text. This research is using Classroom Action Research and the subject of this study were the fourth grade students of SDN 32 Banda Aceh academic year 2015/2016 of that consist of 30 students. This study was conducted in two cycles in which for each cycle consist of two meetings. The data were analyzed descriptively both qualitative and quantitative. The result shows that the application of word scramble technique successfully improve students' reading comprehension ability. Students become more active and enthusiastic in learning reading, students are more willing to express their opinions, and students’ group work is running well. The improvement of students' reading comprehension ability is seen from the number of students who achieved the minimum criteria of pre-test at 36.6%, which it is increased 60% at the first cycle and at the end of the second cycle of 87%. While the average value on pre-treatment is equal to 65.2, the end of first cycle is 70.5, and at the end of second cycle is 78.33. Abstrak Penelitian ini bertujuan untuk memperbaiki kualitas kemampuan membaca pemahaman Siswa Kelas IV SDN 32 Banda Aceh. Dalam mengikuti pembelajaran siswa terlihat kurang bersemangat, hal ini dikarenakan guru dalam mengajarkan materi pembelajaran membaca pemahaman menggunakan cara yang monoton. Guru dalam pembelajaran Bahasa Indonesia hanya memberikan teks bacaan kepada siswa, kemudian siswa disuruh menjawab pertanyaan dari teks bacaan tersebut. Sehingga keterampilan membaca pemahaman siswa masih kurang. Jenis penelitian ini adalah penelitian tindakan kelas (Classroom Action Research), dengan subjek penelitian Siswa Kelas IV SDN 32 Banda Aceh Tahun ajaran 2015/2016. Objek dari penelitian ini adalah kemampuan membaca pemahaman siswa Kelas IV SDN 32 Banda Aceh. Penelitian ini dilaksanakan dalam dua siklus pembelajaran dengan setiap siklus dua kali pertemuan. Data dianalisis secara deskriptif kualitatif dan kuantitatif. Penerapan teknik scramble wacana berhasil memperbaiki proses pembelajaran serta kemampuan membaca pemahaman siswa dapat meningkat. Siswa menjadi lebih aktif dan antusias dalam mengikuti pembelajaran, siswa lebih berani mengungkapkan pendapatnya, serta kerja kelompok berjalan dengan baik. Peningkatan kemampuan membaca pemahaman siswa terlihat dari jumlah siswa yang berhasil mencapai nilai Kriteria Ketuntasan Minimal pada pre-tes sebesar 36,6%, akhir siklus I sebesar 60%, dan pada akhir siklus II sebesar 87%. Sedangkan nilai rata-rata pada pratindakan adalah sebesar 65,2, akhir siklus I sebesar 70,5, dan pada akhir siklus II sebesar 78,33. Kata kunci: Teknik Scramble, Membaca Pemahaman